Strengthening Fiscal Frameworks and Improving the Spending Mix in Small States - Cabezon, Ezequiel (IMF Working Papers; Working Paper ;, 2015)
Reflecting diseconomies of scale in providing public goods and services, recurrent spending in small states typically represents a large share of GDP. For some small states, this limits the fiscal space available for growth-promoting capital spending. Small states generally face greater revenue volatility than other country groups, owing to their exposure to exogenous shocks (including natural disasters) and narrow production bases. With limited buffers, revenue volatility often results in procyclical fiscal policy as the econometric analysis shows. To strengthen fiscal frameworks, small states should seek to streamline and prioritize recurrent spending to create fiscal space for capital spending. The quality of spending could also be improved through public financial management reform and multiyear budgeting.